The accident phenomenon in a naval shipyard - Arcaleni, R; Valentino, M; Fidecicchi, G; Ceccarelli, G (Medicina del lavoro, 1990)
The paper analyses the rate and severity of accidents in a shipyard in the period 1 January-31 December, 1987. Data were collected by consulting the shipyards' accident register, which recorded each single case of injury, and the medical certificates sent to the shipyard management by the worker's physicians. The shipyard employed 996 blue collar workers and 210 white collar workers in 1987, all of whom were subject to obligatory industrial accident insurance. For each of the 1375 accidents that occurred in the period under study, the time, place and cause of the accident and the type and site of the injury were recorded. The aim of the statistical analysis of the data was to assess the risk in each area of the shipyard and the causes of the accidents in relation to the work station and job. The severity rate of injury increased in those workers recently assigned to new jobs; climate had a negative influence since accidents were more frequent in spring/summer. Accident prevention measures are suggested that can be achieved by improving work organisation and by a more appropriate use of personal safety devices.